Developing Suicide Safety Protocols for Qualitative Research as a Universal Equity Practice. (August 2021) - Hawk, Mary; Pelcher, Lindsay; Coulter, Robert W. S.; Henderson, Emmett; Egan, James E.; Miller, Elizabeth; Chugani, Carla
Qualitative research offers a range of approaches to elucidate the health and social experiences of populations and communities that are historically oppressed and repressed, yet is not without ethical and practical challenges that may have unintended consequences and added risks for certain individuals and communities. As a result of experiences of trauma and environmental factors, many oppressed and repressed populations have disproportionately high rates of suicide, but there are no widely accepted standards or best practices for addressing suicidality while conducting qualitative research. We describe an example of a qualitative interview during which a participant reported thoughts of suicide, even though the study topic was not directly related to mental health or suicide. We describe how the research team responded and present a framework for developing suicide safety protocols when conducing qualitative research with oppressed and repressed populations.